Anais Do III Inovagri International Meeting - 2015 2015
DOI: 10.12702/iii.inovagri.2015-a064
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade E Composição Botânica De Tifton 85 Nas Diferentes Estações Do Ano Sob Irrigação

Abstract: RESUMO: O objetivo do trabalho foi avaliar a produtividade e a composição botânica do capim Tifton 85 na presença e na ausência de irrigação durante as quatro estações do ano. O experimento foi conduzido no período de novembro de 2012 a maio de 2013, em uma propriedade de produção leiteira, localizada no município de Mariluz, região Noroeste do Paraná. O delineamento experimental utilizado foi de blocos casualizados em esquema de parcelas subdivididas, com quatro repetições. Nas parcelas foram aplicados os tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
6
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 0 publications
5
6
0
Order By: Relevance
“…These are corroborated with literature, which mentioned accumulations between 55 and 90 kg DM ha -1 day -1 for irrigated Tifton 85 grass (Ribeiro and Pereira, 2011;Gomes et al, 2015a, Sanches et al, 2016. Meanwhile, in the irrigated area the accumulated dry matter has been between 105 and 125 kg DM ha -1 day -1 (Queiroz et al, 2012, Nogueira et al, 2013, Teixeira et al, 2013, Gomes et al, 2015b, Sanches et al, 2016. Sanches et al, 2016 reported yield of 37603.1 and 25457.6 kg ha -1 year -1 in irrigated and non-irrigated areas in a study on Tifton 85, which is consistent with the results of present study.…”
Section: Yield Parameters Of Forage Dry Mattersupporting
confidence: 92%
See 4 more Smart Citations
“…These are corroborated with literature, which mentioned accumulations between 55 and 90 kg DM ha -1 day -1 for irrigated Tifton 85 grass (Ribeiro and Pereira, 2011;Gomes et al, 2015a, Sanches et al, 2016. Meanwhile, in the irrigated area the accumulated dry matter has been between 105 and 125 kg DM ha -1 day -1 (Queiroz et al, 2012, Nogueira et al, 2013, Teixeira et al, 2013, Gomes et al, 2015b, Sanches et al, 2016. Sanches et al, 2016 reported yield of 37603.1 and 25457.6 kg ha -1 year -1 in irrigated and non-irrigated areas in a study on Tifton 85, which is consistent with the results of present study.…”
Section: Yield Parameters Of Forage Dry Mattersupporting
confidence: 92%
“…Meanwhile, in the irrigated area the accumulated dry matter has been between 105 and 125 kg DM ha -1 day -1 (Queiroz et al, 2012, Nogueira et al, 2013, Teixeira et al, 2013, Gomes et al, 2015b, Sanches et al, 2016. Sanches et al, 2016 reported yield of 37603.1 and 25457.6 kg ha -1 year -1 in irrigated and non-irrigated areas in a study on Tifton 85, which is consistent with the results of present study. Thus, it is observed that the irrigation contributes to increasing yield in cycles possibly through favouring the assimilation of available soil and climate resources.…”
Section: Yield Parameters Of Forage Dry Mattersupporting
confidence: 91%
See 3 more Smart Citations